A multigroup analysis of gender in adopting Fintech services in Indonesia - Setiawan, Budi (Institute of Computer Science (IOCS), 2024)
The proliferation of technology, coupled with a substantial population of smartphone users, is revolutionizing how people access financial services in Indonesia. This study investigates the driving factors behind the adoption of Fintech among users in Indonesia by employing an extended Unified Theory of Acceptance and Use of Technology (UTAUT) model integrated with digital financial literacy. Furthermore, this study also evaluates the differences between male and female respondents in adopting Fintech services. This research, which gathered data from 228 participants and analyzed it using Partial Least Square Structural Equation Modeling (PLS-SEM), found that performance expectancy is the primary factor influencing behavioral intention in Indonesia. Use behavior plays a significant role in affecting continuance intention. Furthermore, notable differences were identified between men and women regarding the correlation between performance expectancy and behavioral intention. These findings have implications for Fintech business providers in designing effective strategies aimed at increasing access to financial services and promoting financial inclusion in Indonesia. For policymakers, performing a multi-group analysis on gender and technology adoption is consistent with the United Nations Sustainable Development Goal (UNSDG) number 5, which aims to promote gender equality